2009
DOI: 10.4012/dmj.28.735
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of stainless steel by plasma-based fluorine and silver dual ion implantation and deposition

Abstract: The aims of this study were to modify dental device surface with fluorine and silver and to examine the effectiveness of this new surface modification method. Stainless steel plates were modified by plasma-based fluorine and silver ion implantation-deposition method. The surface characteristics and brushing abrasion resistance were evaluated by XPS, contact angle and brushing abrasion test. XPS spectra of modified specimens showed the peaks of fluoride and silver. These peaks were detected even after brushing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…This process is also used on some of the dental implants to increase the corrosion resistance by forming Ti-N surface. [ 20 ]…”
Section: Surface Modificationsmentioning
confidence: 99%
“…This process is also used on some of the dental implants to increase the corrosion resistance by forming Ti-N surface. [ 20 ]…”
Section: Surface Modificationsmentioning
confidence: 99%
“…It is suggested that ions like F and Ag with antibacterial property can be implanted and deposited on the surface of stainless steel implants with no toxic effect. 30…”
Section: Plasma-sprayed Hydroxyapatitementioning
confidence: 99%
“…Plasma treatment increases surface energy of the implant and there by improves the wetting characteristics as compared to conventional implant surfaces cleaned by using solvents or autoclaving. 9…”
Section: Vacuum Treatmentsmentioning
confidence: 99%